The Effect Of The Pq4r Strategy On The Reading Comprehension Ability Of Grade IV Students Mis Istiqomah Medan - Syakira Ridwan, Fitri; Nirwana Anas (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2025)
The ability to read comprehension is an important skill that must be mastered by elementary school students. This study aims to determine the influence of the PQ4R strategy on the reading comprehension ability of fourth grade MIS Istiqomah Medan students. The research uses a quantitative approach with a one-group pretest-posttest design. The researcher used grade IV students of MIS Istiqomah Medan with 14 students as a research experiment. The instrument used was a reading comprehension essay test. The results showed a significant influence, from the average pretest score of 27.86 to 86.5 in the posttest. The statistical test showed a significance value (2-tailed) with a value of 0.000 which showed a positive influence of the PQ4R strategy. Thus, this strategy has proven to be effective in helping students understand reading more deeply and is suitable for application in Indonesian learning at the elementary school level.